Planʺ vkhoda vʺ bukhtu Brusno, na Onezhskomʺ ozeri︠e︡ sostavlenʺ po sʺemki︠e︡ 1874 goda / Izdanʹ Gidrograficheskimʺ Departmentomʺ M. M. vʺ 1891 g. - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1881)
Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; Pulkovo meridian.; "Masshtabʺ 200 sazh. vʺ di︠u︡ĭmi︠e︡." [Scale 200 sazhens in 1 inch].; "No. 183" -- handwritten bottom right margin Grayscale; 1:14,400